Pola Kepemimpinan Kepala Perpustakaan Dalam Pengelolaan Unit Perpustakaan Di Madrasah Aliyah Negeri 1 Medan - Herlina Hutabarat (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2017)
This is research descriptioan “Pola Kepemimpinan Kepala Perpustakaan Dalam Pengelolaan Unit Perpustakaan di Madrasah Aliyah Negeri 1 Medan”. Purpose method is method kualitative, with technical collection data: interview, observation, and study document. The step description data is arrange dara, unite data, overcast data, provide data, and conclusion. For teching data in experiment credibility, transferability, dependability, and confirmability.This is research: (1) Implement functions library management in to manage unit library the school is already to make year program in referensi books. Head master and head library are involeved arrange year program library. Object planning is manage unit library for student, teacher, staff, and guest. (2) head library leadership is manage unit library very good. This is matter at look from style leadership, communication, and to make decision.(3) factor carry in to manage unit library human (librarian), BOS books. (4) factor obstacle in to manage unit library donation, medium library, the training minus, and minimum books collection. The suggestion for stakeholders cooperation for level to manage and medium library School Aliyah Negeri 1 Medan.